If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + 10c = 3c + 3 Reorder the terms: 10 + 10c = 3 + 3c Solving 10 + 10c = 3 + 3c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3c' to each side of the equation. 10 + 10c + -3c = 3 + 3c + -3c Combine like terms: 10c + -3c = 7c 10 + 7c = 3 + 3c + -3c Combine like terms: 3c + -3c = 0 10 + 7c = 3 + 0 10 + 7c = 3 Add '-10' to each side of the equation. 10 + -10 + 7c = 3 + -10 Combine like terms: 10 + -10 = 0 0 + 7c = 3 + -10 7c = 3 + -10 Combine like terms: 3 + -10 = -7 7c = -7 Divide each side by '7'. c = -1 Simplifying c = -1
| 0=t^2-t-4 | | 3x-5y=-12solvey | | 10+10c=3c+c | | 3n^2-21=2n | | 22.9+3.00= | | 6x-20=3x+13 | | 2r^2-9r=-7 | | -5-t=21 | | 8=10+3x | | 2(2b+10)=12(b-1) | | 15x+8=20+3x | | 4(2x-2y)+5(2y-x)= | | S=2(3.14159)r^2+2(3.14159)rh | | x^2+6x+10=5 | | 9-9a= | | .75x=20 | | -5+3x=-14 | | (lnx+1)(lnx-1)=0 | | -4(r+8)=-55 | | 8x-2(2x-3)=12+2x | | 7-5v=-4v | | 5(2x+1)-3(x-3)=63 | | x^2+19x+65=0 | | -9(-2w+3x-6)= | | 1=-7x | | 40+9-30+2= | | 15x+2=6x+10 | | 1059/10=18/1(14/13x) | | -1=-7x | | 6.2h-0.4=2.7 | | 3a+18=3(2a+3) | | X^2+12x-43=4x+5 |